The influence of thickness layers on the efficiency of MAPI solar cells - Aziz, Issa Mahdi; Salih, Raad Nasrullah; Haji, Akram Ali (Eximia, 2023)
The recycling of vehicle batteries to produce Perovskite solar cells (PSCs) is done in this study using a simple technique. attempting to remove certain objects or things from the surroundings. However, by recycling vehicle batteries, we may avoid disposing of hazardous battery components and offer a different method a widely accessible source of Pb for making PSCs. On an FTO glass substrate, perovskite solar cells (PSCs) were created using a two-step spin coating solution process. The precursor (CH3NH3PbI3) is made up of lead iodide (PbI2) and methyl-ammonium iodide (CH3NH3I). Investigated were the photovoltaic performance of PSCs and the impact of the perovskite layer's chemical composition on that performance.